Comparison of chemically estimated depositional ages with zircon SHRIMP ages from metacarbonate rocks in the Sør Rondane Mountains, East Antarctica - N., Otsuji; M., Satish-Kumar; T., Hokada; K., Horie; A., Kamei; G.H., Grantham; N., Tsuchiya; T., Kawakami; M., Ishikawa (2012)
第3回極域科学シンポジウム/第32回極域地学シンポジウム 11月30日（金） 国立極地研究所 ３階ラウンジ conference object